Bacteroides bacteremia complicating otogenic Lemierre's syndrome. (September 2016) - Lawrence, Karena G.; Lee, Benjamin; Dewar, Stephanie; Shah, Jay; Dohar, Joseph E.; Nowalk, Andrew J.; Martin, Judith M.
Abstract: Lemierre's syndrome is a complex infection involving oropharyngeal sources leading to septic jugular thrombophlebitis. Otogenic variants may arise from complicated ear disease and involve cranial venous sinuses. We describe a case of a 9 year boy with chronic suppurative otitis media leading to mastoiditis, cranial venous sinus and jugular vein thrombophlebitis, and Bacteroides bacteremia. Both the pathogen and the extent of venous involvement were unusual in this case. Otogenic Lemierre's syndrome is a serious infection associated with significant morbidity which should be considered in any child with otogenic findings and septic thrombophlebitis.